EFEKTIVITAS PEMBERIAN TEKNIK MASSAGE EFFLEURAGE DAN TEKNIK MASSAGE CONTERPRESSURE TERHADAP RASA NYERI PERSALINAN NORMAL PADA PRIMIGRAVIDA DI LANGSA TAHUN 2017 - Elly Susilawati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
Labor pain is a manifestation of contractions of the uterine muscles. Pain in childbirth if left untreated will increase anxiety, tensionand stress. Increased consumption of body glucose in maternity mothers who experience stress causes fatigue and catecholamine secretion that inhibits uterine contractions, which causes prolonged labor which ultimately causes anxiety in the mother, increased pain and prolonged stress. Massage can be used during labor and may be an effective pain reliever. The common massage technique is effleurage and Conterpressure. The aim this studyto determine the effectiveness of providing Effleurage Massage and Conterpressure Massage techniques in Active Phase Pain Reduction during normal labor in Primigravida mother at Eva Repelitamidwifery practice and Rusmalanitamidwifery practice Langsa City. Design of this study was quasi experimental design with posttest only control group design in the form of pain scaling in the first stage of active labor, conducted at Eva Repelita, Am.Keb midwifery practice and Rusmalanita Am.Keb midwifery practice in February to April 2017 Langsa City. The sample in this study were mothers, whom divided into two groups numbered 16 people, thus the total sample was 32 people. Data analysis techniques used are Univariate and Bivariate analysis using Paired T-Test The result of this study the mean pain scale in active phase of normal labor in Primigravida mothers, with Effleurage Massage Technique was 2 with SD 2.44 deviation, while the mean pain scale with Massage Conterpressure technique is 6 with SD 6.36 deviation. While the results of the Statistical Test using Paired T-test obtained P value of 0,000, that the Effleurage Massage technique was more effective than the Conterpressure Massage technique in reducing labor pain during active phase. Conclusions: It can be concluded that Effleurage Massage technique was more effective than Conterpressure Massage technique in reducing labor pain during the active phase.